In vitro effect of comercial pesticides on Trichoderma harzianum strain A- 34 - Castellanos González, Leónides; Lorenzo Nicao, María E.; Muiño, Berta Lina; Hernández Pérez, Ricardo; Guillen Sánchez, Dagoberto (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2015)
The work aims to evaluate the in vitro effect of six commercial pesticides on the mycelia growth, the spore production and conidia germination of Trichoderma harzianum strain A-34. The assay was carried out with the following products: folpet (Folpam 80 PH), zineb (Zineb 80 PH), mancozeb (Mancozeb 75 PH), cipermetrina (Cipermetrina 10 EC), lambda cialotrina (Karate 5 EC) and abamectina (Abamectin 1.8 EC) to the concentrations of 10, 100, 200, 500, 1000 and 2000 mg L-1. The growth inhibition of the fungus colony, the effect of the pesticides on the spore production and the conidia germination were evaluated. The pesticides were classified according to their toxicity on the antagonist by the OILB scale and their compatibility according to the T value. The folpet, mancozeb and zineb fungicides, and the abamectina insecticide have inhibitory effect on the growth of the mycelia of the fungus T. harzianum, and they are classified as lightly toxic. However, when considering the T value, zineb is classified as very toxic, and mancozeb and folpet as moderately toxic, while the insecticides are not toxic to the antagonist. Fungicides affect the germination of the antagonist’s conidia but insecticides do not.